1998
DOI: 10.1128/mcb.18.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Negative Cofactor NC2 in Active Repression by Zinc Finger-Homeodomain Transcription Factor AREB6

Abstract: The transcription factor AREB6 contains a homeodomain flanked by two clusters of Krüppel type C 2 H 2 zinc fingers. AREB6 binds to the E-box consensus sequence, CACCTGT, through either the N-or the C-terminal zinc finger cluster. To gain insights into the molecular mechanism by which AREB6 activates and represses gene expression, we analyzed the domain structure of AREB6 in the context of a heterologous DNA-binding domain by transient-transfection assays. The C-terminal region spanning amino acids 1011 to 1124… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 63 publications
1
42
0
Order By: Relevance
“…p53-mediated activation of AFP expression in NIH 3T3 cells which lack HNF-3 argues against recruitment of ubiquitous, general repressors of transcription by p53 binding. This mode of transcription repression has been described for general transcription repressor NC2 tethering via DNA-bound AREB6 Zn-finger/homeodomain protein (41). However, our results indicate that repression of AFP may involve tissue-specific corepressors of transcription that are targeted by p53 binding within the developmental repressor domain.…”
Section: Resultssupporting
confidence: 67%
“…p53-mediated activation of AFP expression in NIH 3T3 cells which lack HNF-3 argues against recruitment of ubiquitous, general repressors of transcription by p53 binding. This mode of transcription repression has been described for general transcription repressor NC2 tethering via DNA-bound AREB6 Zn-finger/homeodomain protein (41). However, our results indicate that repression of AFP may involve tissue-specific corepressors of transcription that are targeted by p53 binding within the developmental repressor domain.…”
Section: Resultssupporting
confidence: 67%
“…It has recently been reported that changes within the ZEB1 gene are responsible for the pathogenesis in a large percentage of patients with this corneal disorder (Krafchak, et al, 2005). ZEB1 maps to chromosome 10p11.2, comprises 9 exons and encodes a transcription factor that is organized in multiple functional domains starting with N-terminal zinc finger clusters (172-292), followed by a homeodomain (581-640), repression domain (754-901), C-terminal zinc finger clusters (905-981) and acidic activation domain (1011-1124) (Ikeda, et al, 1998). We have identified four novel disease mutations within the ZEB1 gene in subjects with PPCD, in four of ten unrelated PPCD families.…”
Section: Discussionmentioning
confidence: 99%
“…Class IV co-factors include those that covalently modify nucleosomes. Members of this class are represented here by the histone acetylases CBP/p300, GCN5, P/CAF, and the SRC-1-related p160 family Yang et al 1996;Grant et al 1997;Spencer et al 1997), as well as the histone deacetylases HDAC-1 and HDAC-2 (rpd3), and Chen et al 1994;Ge and Roeder 1994;Sun et al 1994;Yokomori et al 1994;Chi et al 1995;Hansen and Tjian 1995;Verrijzer et al 1995;Dikstein et al 1996a;Mermelstein et al 1996;Mizzen et al 1996;Brandsen et al 1997;Ikeda et al 1998;Malik et al 1998). b (Triezenberg et al 1988;Liu and Green 1990;Wilson et al 1993;Jarriault et al 1995;Luo and Roeder 1995;Strubin et al 1995;Jimenez et al 1997;Nibu et al 1998;.…”
Section: Classifying a Profusion Of Co-activators And Co-repressorsmentioning
confidence: 99%